Differences of tumor-recruiting myeloid cells in murine squamous cell carcinoma influence the efficacy of immunotherapy combined with a TLR7 agonist and PD-L1 blockade. (April 2019) - Tachinami, Hidetake; Nishii, Naoto; Xia, Yulong; Kashima, Yoshihisa; Ohno, Tatsukuni; Nagai, Shigenori; Li, Lixin; Lau, Walter; Tomihara, Kei; Noguchi, Makoto; Azuma, Miyuki
Highlights: Two murine models of SCC show different tumor-infiltrating CD11b + Gr-1 + phenotypes. NR-S1 and SCCVII tumors recruit neutrophil- and macrophage-like cells. Resiquimod plus PD-L1 blockade has no effect against NR-S1 tumors. Depletion of CD11b + Gr-1 + cells increases the treatment efficacy. The tumor-recruiting myeloid cell status influences the efficacy of immunotherapy. Abstract: Objectives: The immune status of the tumor microenvironment has a marked impact on clinical outcomes. Here we examined the immune environments of tumor-infiltrating leukocytes (TILes) in two murine models of squamous cell carcinoma and compared the effects of immunotherapeutic agents, including a TLR7 agonist and an immune checkpoint inhibitor, and a chemotherapeutic agent, gemcitabine, in these models. Materials and methods: TILes from NR-S1- and SCCVII-grafted mice were analyzed by flow cytometry. NR-S1-inoculated mice received resiquimod (a synthetic TLR7 agonist), an anti-PD-L1 antibody, or both, and tumor growth and TILs were examined. Gemcitabine was administered to deplete CD11b + cells. Results: More than 50% of TILes from NR-S1- and SCCVII-inoculated mice were CD11b + Gr-1 + cells. A major fraction of NR-S1 CD11b + cells was Ly6G high Ly6C low-nega F4/80 − tumor-associated neutrophils (TANs) and the majority of SCCVII CD11b + cells were Ly6G low Ly6C − F4/80 + tumor-associated macrophages. NR-S1 TANs did not express MHC class II and CD86, but did express reactive oxygen species and PD-L1. Resiquimod, alone and in combination with an anti-PD-L1 antibody, did not regress NR-S1 tumors, but the combination increased the CD8/regulatory T cell-ratio, and IFN-γ and PD-1 expression in CD8 + TILes. Pre-administration of low-dose gemcitabine prior to the combination treatment suppressed the progression of NR-S1 tumors. Conclusions: NR-S1 tumors with abundant recruitment of TANs were resistant to treatments with a TLR7 agonist, alone and in combination with PD-1 blockade, and required an additional gemcitabine treatment. The phenotype and status of tumor-infiltrating CD11b + myeloid cells may influence the efficacy of immunotherapeutic agents.